Three Different Approaches for the Clarification of the Interactions between Lipoproteins and Chondroitin-6-sulfate - Lipponen, Katriina (2011)
Two different experimental approaches were used for obtaining a comprehensive view and understanding of the interactions between apolipoprotein B-100 (ApoB-100) of low-density lipoprotein and apolipoprotein E (ApoE) of high-density lipoprotein and chondroitin-6-sulfate (C6S) of arterial proteoglycan. The techniques employed were partial filling affinity capillary electrophoresis (PF-ACE) and continuous flow quartz crystal microbalance (QCM). In addition, molecular dynamic (MD) simulations were used to provide a supportive visual insight into the interaction mechanism. A new tool for analysis of QCM-data was utilized, i.e., adsorption energy distribution calculations, which allowed a deeper understanding of the interactions, especially at different temperatures. The PF-ACE technique probed mainly the strong adsorption interactions whereas in the MD calculations short-and long-range interactions could be distinguished. Although there are differences in the techniques, a pretty good agreement was achieved between the three approaches for the interaction of 19 amino acid peptide of ApoB with C6S giving log affinity constants of 4.66 by QCM, 5.02 by PF-ACE, and 7.39 by MD, and for 15 amino acid peptide of ApoE with C6S 5.34 by QCM, 5.28 by PT-ACE, and 4.60 by MD at physiological temperature 37.0 °C.